2009
DOI: 10.1007/s10802-009-9370-9
|View full text |Cite
|
Sign up to set email alerts
|

Equivalency for Father and Mother Ratings of the ADHD Symptoms

Abstract: The study used multiple-group confirmatory factor analysis (CFA) and multiple indicators multiple causes (MIMIC) procedures to examine the measurement and construct equivalencies for father and mother ratings of ADHD symptoms, recoded as binary scores. Fathers (N = 387) and mothers (N = 411) rated their primary school-aged children on the Disruptive Behavior Rating Scale (Barkley & Murphy, 1998). For the multiple-group CFA analyses, the results involving differences in practical fit indices supported full meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Furthermore, recent studies using IRT models have also shown that this symptom has very low threshold compared with the other symptoms and also relatively low item information function (comparable with reliability) across the trait spectrum, thereby questioning its ability to measure the IA trait (Gomez, 2008a, 2008b; Gomez, Vance, & Gomez, 2010). Also, this symptom has shown noninvariance across father and mother ratings (Gomez, 2010) and across ethnic and national groups (Gomez, 2009). Together, these findings raise the possibility that this symptom may be “problematic” for diagnostic purpose, thereby raising the need for closer scrutiny for inclusion in DSM-V .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies using IRT models have also shown that this symptom has very low threshold compared with the other symptoms and also relatively low item information function (comparable with reliability) across the trait spectrum, thereby questioning its ability to measure the IA trait (Gomez, 2008a, 2008b; Gomez, Vance, & Gomez, 2010). Also, this symptom has shown noninvariance across father and mother ratings (Gomez, 2010) and across ethnic and national groups (Gomez, 2009). Together, these findings raise the possibility that this symptom may be “problematic” for diagnostic purpose, thereby raising the need for closer scrutiny for inclusion in DSM-V .…”
Section: Discussionmentioning
confidence: 99%
“…First, the gender of parent respondents was unknown, but bias from parental gender is unlikely. Although some research indicates that small differences exist between the ratings of mothers and fathers (Gomez, 2010), mothers more frequently than fathers refer children for mental and physical health services and interact with school personnel (Phares, Lopez, Fields, Kamboukos, & Duhig, 2005). Thus, the majority of parental respondents were likely mothers.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, previous studies examined community samples of children in which participants were not formally assessed or diagnosed with ADHD (McLoughlin et al, 2011; Molina, Smith, & Pelham, 2001; Ullebø et al, 2012), used relatively small sample sizes (Healey et al, 1993), did not examine the suitability of three-factor models (McLoughlin et al, 2011; Molina et al, 2001), allowed error terms to correlate with one another to achieve fit (Collett, Crowley, Gimpel, & Greenson, 2000), or used exploratory rather than confirmatory factor analysis (CFA) to determine latent symptom dimensions (McLoughlin et al, 2011; Thaler, Bello, & Etcoff, 2013). Furthermore, some studies combine both mothers and fathers into one analysis, despite findings that parents differ with regard to ratings of symptom severity in ADHD (Gomez, 2010; Langberg et al, 2010; Sollie, Larsson, & Mørch, 2013). Differences in parental ratings could have the potential to alter factor structure.…”
mentioning
confidence: 99%